Interpretation and Body Awareness Strategies in Guidance and Counseling Psychology - Putra Suharnadi; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
Psychoanalytic counseling aims to help individuals interpret facts, deepen the meaning of life values ​​personally, socially, now and in the future. Psychoanalytic counseling with interpretation techniques helps individuals to develop mental health, change attitudes and behavior towards good moral development. Interpretation (interpretation) is a skill/technique used by counselors which means or because the client's behavior is interpreted/suspected and understood by communicating it to the client (Supriyo & Mulawarman, 2006). Interpretation also makes clients understand themselves better through the counselor's interpretation (Hariastuti & Darminto, 2007). According to Supriyo & Mulawarman (2006) the purpose of interpretation is to help clients understand themselves better if the client is willing to consider it with an open mind. There are three types of interpretation, namely checking information, single interpretation, multiple interpretation. Meanwhile, Body Awareness techniques include Recognition of the Body and Feelings, Expressing the Anger Dimension, Breathing Methods, Expression, Expressing the Strength Dimension, Expressing the Weakness Dimension, Gendlin Focusing.